1972
DOI: 10.2134/agronj1972.00021962006400040007x
|View full text |Cite
|
Sign up to set email alerts
|

Winter Turf Development on Dormant Bermudagrass as Influenced by Summer Cultivation and Winter N Fertilization1

Abstract: Overseeded winter turf on dormant bermudagrass is an important practice in providing live turf for a large portion of the year. It has been observed that as vigorous bermudagrass becomes older satisfactory winter turf is more difficult to establish and maintain. Previous research has shown that cultivation of bermudagrass immediately prior to overseeding cool season turfgrasses has improved winter turf. However, no work has been reported showing the effects of bermudagrass summer cultivation on overseeded wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
1
2
1
Order By: Relevance
“…The Lm treatment similarly reduced C 4 verdure in Cynodon the same year (Table 5). These results conflict with numerous reports that link the early decline of C 3 grasses to earlier recovery of the host turf (Schmidt and Shoulders, 1972; Dunn et al, 1994; Richardson, 2004). Poor C 4 recovery despite removal of competition from ryegrass has been speculatively attributed to allelopathic chemical release during C 3 plant death (Kopec et al, 2001).…”
Section: Resultscontrasting
confidence: 94%
“…The Lm treatment similarly reduced C 4 verdure in Cynodon the same year (Table 5). These results conflict with numerous reports that link the early decline of C 3 grasses to earlier recovery of the host turf (Schmidt and Shoulders, 1972; Dunn et al, 1994; Richardson, 2004). Poor C 4 recovery despite removal of competition from ryegrass has been speculatively attributed to allelopathic chemical release during C 3 plant death (Kopec et al, 2001).…”
Section: Resultscontrasting
confidence: 94%
“…The improved establishment in 2007 and 2008 from pre‐plant aerification is similar to previous research in which aerification plus soil‐topdressing enhanced establishment of annual ryegrass in a bermudagrass fairway turf (Schmidt and Shoulders, 1972). However, this is different than a previous report by Schmidt and Blaser (1962), in which verticutting was more effective than aerification in establishing overseeding grasses into a bermudagrass putting green.…”
Section: Resultssupporting
confidence: 87%
“…Schmidt and Shoulders (1972) emphasized the importance of removing bermudagrass thatch to promote cool‐season overseeding establishment during winter months, as thatch removal would increase seed to soil contact and improve overseeding turf establishment (Schmidt and Blaser, 1962). Schmidt and Blaser (1962) also found that verticutting in multiple directions was more effective at promoting overseeding turf establishment than aerification, but this may have been due to the close mowing height (0.8 cm) used in their study for a bermudagrass putting green.…”
Section: Resultsmentioning
confidence: 99%
“…Although germination increased over time, no differences existed due to treatment (data not shown). Schmidt and Shoulders (1972) suggested that C. dactylon thatch removal via vertical mowing would result in greater seed‐to‐soil contact of the overseeded species and thus increased establishment. In the current study, vertical mowing in one direction did not improve overseed establishment over the untreated control.…”
Section: Resultsmentioning
confidence: 99%